The correlation and influence of intercultural communication in creating social harmonization between ethnicities - Rosy Febriani Daud; Agung Prihatmojo (The Indonesian Journal of Communication Studies, 2021)
Different cultural backgrounds can cause conflict and friction. Individual differences are the cause, differences in understanding and expectations. The impact of the development of the times requires humans to eliminate the group ego for a harmonious relationship between human beings. This is in the diversity of tribes that require the community to live in a harmonious relationship. This research has the title Correlation Regarding the Effect of Intercultural Communication in Creating Inter-Ethnic Harmonization. The aim is to see the extent of the influence of intercultural communication in creating harmonization between the Sumendo and Sundanese ethnic groups in Sindang Marga Village, Tanjung Raja District, North Lampung Regency. The problem formulation of this research is how the influence of intercultural communication in creating harmonization between the Sumendo and Sundanese ethnic groups in Sindang Marga Village, Tanjung Raja District, North Lampung Regency. The method used in this study is the quantitative method. The results of this study were 10 respondents (20%) in the high category and 8 respondents in the medium category (16%), as many as 7 respondents (14%) in the low category and as many as 5 respondents. (10%) are in the very low category. Thus it can be concluded that most respondents are in the category of very high intercultural communication influence. Meanwhile, from 50 respondents, 21 people (42%) answered the question of inter-ethnic social harmonization variables and were in the very high category. A total of 9 respondents (18%) were in the high category, as many as 10 respondents (20%) were in the medium category, as many as 5 respondents (10%) were in the low and very low categories. Thus it can be concluded that most respondents are in the category of very high inter-ethnic social harmonization.